Acute kidney injury caused by COVID-19: a literature review (Research, Society and Development, 2023)
Introduction: In December 2019, a series of pneumonia cases were observed in Wuhan, China. Quickly, thousands of patients developed the same condition and, later, the causal agent was identified: severe acute respiratory syndrome coronavirus (SARS-CoV-2). Among the organic dysfunctions related to COVID-19, hypoxemic respiratory failure was highlighted, but acute kidney injury (AKI) has also been widely reported. Glomerulonephritis, rhabdomyolysis, and nephrotoxic drugs are also associated with kidney damage in COVID-19 patients. Objective: The present research aims to exemplify and understand the association of acute kidney injury (ACL) in patients affected by SARS-CoV-2. ACL is treated as a serious factor directly affecting the health of the patient affected by the sars-cov-2 infection, in the midst of a COVID pandemic and in the face of an increase in the number of cases, the clinical study of the disease became necessary. LCA in these cases to help in the management of the patient, identification of risk factors to optimize diagnosis and treatment, can thus give a good prognosis to the patient. Methodology: this is an integrative literature review carried out using the PICO strategy, which determines current knowledge on a specific topic. Pubmed, LILACS and SciELO data sources were used to search the full articles, which were chosen according to inclusion and exclusion criteria. In the end, 13 articles were found as a final sample, for the present study to be carried out. Results and Discussion: : Systemic endothelial dysfunction is caused by an abrupt increase in cytokine synthesis, especially IL-6, IL-2 and TNF-alpha, during an infection, causing immunological dysregulation. This, in particular, also influences a state of hypercoagulability that the patient develops, which results in a depletion of the intravascular volume, which leads to hypotension that generates renal hypoperfusion. Consequently, the result is prerenal AKI, which has acute tubular necrosis (ATN) as the most common histopathological finding in kidney biopsies. Conclusion: Therefore, it was observed, through recent studies, that there is a great renal contribution to the increase in mortality in patients infected with SARS-CoV-2, and renal complications are one of the main factors of worse prognosis in these individuals.